Corruption, greed, and the public good in the Mariana Islands, 1700-1720 - Coello, Alexandre (Philippine studies : historical and ethnographic viewpoints, 2013)
"This article discusses the disintegrating factors generated by Spanish colonial rule in the Marianas in the early eighteenth century-corruption by colonial officials, ineffective defense against other European powers, precipitous decline in the native population--in a context in which the archipelago's future as a Spanish outpost was debated in religious and political circles in Manila and Madrid. The article focuses on the governorship of Juan Antonio Pimentel, whose immorality as well as oppression of the Chamorros were denounced by the Jesuits. The punishment for Pimentel's corruption and greed was meant to reassert Spain's authority and appreciation for the Marianas as a strategic possession."